Three-Dimensional Hierarchical Nanostructured Cu/Ni–Co Coating Electrode for Hydrogen Evolution Reaction in Alkaline Media - Wang, Ning; Hang, Tao; Chu, Dewei; Li, Ming (Nano-Micro Letters, 2015)
In this work, three-dimensional hierarchical nickel–cobalt alloy coating for hydrogen evolution cathode was fabricated by electrodeposition processes. The coatings’ morphology evolves from sea cucumber-like nanostructure to caterpillar-like one with the increase of cobalt content. A large amount of nanometric “steps,” served as the active sites for hydrogen evolution reaction, were observed. According to Tafel polarization measurements, the exchange current density of the as-synthesized coating with hierarchical nanostructure was 21.9 times compared with that of flat nickel coating. In addition, the hierarchical coating also displayed good electrochemical stability from the galvanostatic test.